Comparative analysis of MCDM methods for ranking renewable energy sources in Taiwan. (September 2018) - Lee, Hsing-Chen; Chang, Ching-Ter
Abstract: Multi-criteria decision making (MCDM) methods are becoming increasingly popular in solving energy selection problems because these problems involve multiple and often conflicting criteria. This paper presents comparative analysis of ranking renewable energy sources (RES) for electricity generation in Taiwan using four MCDM methods - WSM, VIKOR, TOPSIS, and ELECTRE. The Shannon entropy weight method is used to assess the importance of each criterion for the ranking of RES. After that, four MCDM methods are utilized for quantitative evaluation to rank all available RE alternatives. From the weights estimation results, efficiency is the first priority in all evaluation criteria, followed by job creation, operation, and maintenance cost. The purpose of this study is to rank the priorities of various RES and propose recommendations for Taiwan's RE development. The ranking results show that hydro is the best alternative in Taiwan, followed by solar, wind, biomass and geothermal. Furthermore, sensitivity analysis of the weights was conducted considering the ranking results heavily depend on the criteria weight. The results of sensitivity analysis indicated that when financial or technical aspects are focused upon, hydropower is the best RES because its technology is the most mature and the cost is the lowest in Taiwan. In addition, from an environmental perspective, wind energy is the best choice, and from the social perspective, solar PV is the best choice. The findings of this study can provide useful information to energy decision makers and serve as a reference for Taiwan's energy policy. Highlights: MCDM methods for ranking renewable energy sources. Renewable energy policies in Taiwan. Which Criteria are required for ranking renewable energy sources.